Studies on eimeriosis in birds. Isolation of Eimeria sp. n. In paraqueets (Melopsittacus ondulatus) - Brada, Wilhelm (Pesquisa Agropecuaria Brasileira, 2024)
The author describes an Eimeria sp. n. in paraqueets, whose occurrence in these birds has not yet been mentioned in the literature. The author herewith hopes to have contributed to the study of eimeriosis in Psitacidae.